Nation and state in late Imperial Russia nationalism and russification on the western frontier, 1863 - 1914 - Weeks, Theodore R. 1959- (Northern Ill. Univ. Press, 1996)
If one were to pick a single explanation for the fall of the tsarist and Soviet empires, it might well be Russia's inability to achieve a satisfactory relationship with non-Russian nationalities. Perhaps no other region demonstrates imperial Russia's "national dilemma" better than the Western provinces and Kingdom of Poland, an extensive area inhabited by a diverse group of nationalities, including Poles, Jews, Ukrainians, Belorussians, Russians, and Lithuanians. Taking an in-depth look at this region during an era of intensifying national feeling. Weeks shows that the Russian government, even at the height of its empire, never came to terms with the question of nationality. Drawing upon little-known Russian and Polish archives, Weeks challenges widely held assumptions about the "national policy" of late imperial Russia and provides fresh insights into ethnicity in Russia and the former Soviet Union. He demonstrates that, rather than pursuing a plan of "russification," the tsarist government reacted to situations and failed to initiate policy. Extensively researched and path-breaking in its findings, Nation and State in Late Imperial Russia will interest historians, social scientists, and general readers concerned with national identity in Russia and Eastern Europe.